Thermal, magnetic field- and stress-induced transformation in Heusler-type Co-Cr-Al-Si shape memory alloys. (August 2018) - Odaira, Takumi; Xu, Xiao; Miyake, Atsushi; Omori, Toshihiro; Tokunaga, Masashi; Kainuma, Ryosuke
Abstract: The phase diagram, including the martensitic and magnetic transformations, was determined by thermoanalysis and thermomagnetization measurements in the Cox Cr79-x Al10.5 Si10.5 section of the Co-based Heusler shape memory alloy. Magnetization measurements under pulsed magnetic fields were conducted and magnetic field-induced reverse martensitic transformation was clearly observed at room temperature. A superelastic behavior was obtained in the Co55.7 Cr23.3 Al10.5 Si10.5 alloy in the temperature range of 198 to 423 K. The critical stress for martensitic transformation was found to show a negative temperature dependence at temperatures lower than approximately 310 K due to the magnetic effect despite the normal temperature dependence at higher temperatures. Graphical abstract: Unlabelled Image